Wound bed preparation and TIME - Leaper, David (Henry Stewart Talks, 2014)
TIME acronym for managing wound bed preparation 10 years old; needs updating, Awareness of evidence based medicine and need for more quality research, Guidelines still needed; depend on best available evidence and “expert”consensus, 10 year developments considered, Tissue developments: new debridement methods, negative pressure therapy (NPT), Infection developments: better understanding of microbiology, biofilms and antiseptics, antimicrobial therapy and new dressings, Moisture control: improvements with better dressing management and NPT, Edge: accurate monitoring and adjunctive therapies, TIME part of holistic care: TIME revisited in International Wound Journal 2012; 9 (supplement)- the focus expanded and still evolving